(untitled) (Journal of Legal Studies, 2022)
In 2019, the Romanian legislator regulated for the first time, in the content of O.G. no. 6/2019, the legal institution of the restructuring of budgetary claims on the establishment of fiscal facilities. After that, a series of successive normative acts were adopted, meant to prolong the effects of the initial normative act, but also to bring new and necessary clarifications to the content of this legal institution and the procedure for its development from the moment of initiation until the final extinguishment of its effects on the public budget and the patrimony of the involved budgetary debtor. As we have already shown in the content of the present paper, the analysis of the way in which the restructuring of budgetary claims is regulated has allowed us to draw a series of conclusions concerning this legal institution: a. the restructuring of the budgetary claims is a relatively new legal institution that has been adopted through a normative act other than the Fiscal Procedure Code, which it does not, directly and explicitly, amend or supplement, but indirectly by the fact that it can interfere in the conduct of the fiscal procedure, as well as by the fact that it refers to fiscal law institutions regulated by the Fiscal Procedure Code and which thus bears substantial changes; b. the restructuring of the budgetary claims is essentially different from the other forms of financial support established by the provisions of the Fiscal Procedure Code and in particular from the payment facilities designed to provide the budgetary debtor with a grace period in order to obtain the funds necessary to extinguish by payment his obligations to the public budgets. It is also different from the cancellation of tax claims established by the Fiscal Procedure Code because it becomes applicable when the collection of tax receivables becomes useless, inefficient, or impossible. c. although it differs from the rescheduling and adjournment of payment, or the cancellation of tax claims, however, in regulating the restructuring of budgetary claims, the legislator appeals to them themselves, in the form in which they were established in the provisions of the Fiscal Procedure Code.d. the local tax authorities have the right to decide (they are not obliged by law to do so) if they use this legal institution, in the process of collecting the debts due to the budgets they manage;e. in terms of content, the restructuring refers to any kind of budgetary claim (due to the general consolidated budget), in connection with which enforceable titles have also been issued (i.e. the claim has become certain and demandable).